2018
DOI: 10.1016/j.jpeds.2018.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Adversity with Height Stunting Is Associated with Cardiometabolic Risk in Adolescents Independent of Body Mass Index

Abstract: Objective To evaluate cardiovascular and metabolic function in youths adopted internationally from orphanages/institutions (postinstitutionalized) who were height-stunted at adoption. Study design A total of 30 postinstitutionalized youths (age, 9-18 years; body mass index [BMI] percentile, 7.2-90.4) who were height-stunted at adoption were compared with age- and BMI percentile-matched youths (n = 90). Measurements included total body fat and visceral adipose tissue (dual radiograph absorptiometry), arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 55 publications
1
14
1
Order By: Relevance
“…Our results suggest that neonatal antibiotic administration may have detrimental consequences. Impaired childhood growth is known to be associated with poor neurodevelopmental outcomes 35 , 36 and increased occurrence of cardiometabolic risk factors in later life 37 , 38 . Our results corroborate previous studies 8 , 9 , 14 indicating an association between antibiotic use in infancy and early childhood and increased BMI and thus suggests that the effect of antibiotics on child growth is dependent on the age at which the exposure occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that neonatal antibiotic administration may have detrimental consequences. Impaired childhood growth is known to be associated with poor neurodevelopmental outcomes 35 , 36 and increased occurrence of cardiometabolic risk factors in later life 37 , 38 . Our results corroborate previous studies 8 , 9 , 14 indicating an association between antibiotic use in infancy and early childhood and increased BMI and thus suggests that the effect of antibiotics on child growth is dependent on the age at which the exposure occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we cannot be certain that our findings would not have been modified by adiposity. It should be noted that compared to adults, obesity in childhood may be less chronic and therefore potentially less of a strong confounder with metabolic disruption [80] and psychopathology [81]. Other important confounders include parental mental health and medication use by study subjects.…”
Section: Discussionmentioning
confidence: 99%
“…These studies document that childhood adversities are associated with hypertension (Danese et al, 2009; Stein et al, 2010; Reid et al, 2018; Doom et al, 2019), higher BMI (Doom et al, 2019), ischemic heart disease (Dong et al, 2004) and myocardial infarction (Fuller-Thomson et al, 2012). Adverse childhood experience may alter serum lipid/lipoprotein profiles as adults with ELS may have elevated serum TG, LDL-cholesterol and TC as well as low HDL-cholesterol (Danese et al, 2009; Spann et al, 2014; Reid et al, 2018; Doom et al, 2019). Furthermore, a recent study reported that the different trauma types can be associated with specific changes in serum levels, i.e., physical and sexual abuse were associated with high LDL-C and low HDL-C, and childhood neglect with raised TG and low HDL-C (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A vast number of studies report that early life adversity may increase cardiovascular risk factors and the occurrence of CVD (Batten et al, 2004; Dong et al, 2004; Goodwin and Stein, 2004; Danese et al, 2009; Fuller-Thomson et al, 2010, 2012; Korkeila et al, 2010; Stein et al, 2010; Scott et al, 2011; Rich-Edwards et al, 2012; Basu et al, 2017; Murphy et al, 2017; Reid et al, 2018; Doom et al, 2019; Obi et al, 2019). These studies document that childhood adversities are associated with hypertension (Danese et al, 2009; Stein et al, 2010; Reid et al, 2018; Doom et al, 2019), higher BMI (Doom et al, 2019), ischemic heart disease (Dong et al, 2004) and myocardial infarction (Fuller-Thomson et al, 2012). Adverse childhood experience may alter serum lipid/lipoprotein profiles as adults with ELS may have elevated serum TG, LDL-cholesterol and TC as well as low HDL-cholesterol (Danese et al, 2009; Spann et al, 2014; Reid et al, 2018; Doom et al, 2019).…”
Section: Discussionmentioning
confidence: 99%